Informix stored procedure programming - Gonzales, Michael L. (Prentice Hall PTR Informix Press, 1996)
This book helps the reader understand Informix stored procedures, which can be used to dramatically improve the performance of SQL code, tighten security, reduce maintenance of permissions, and maximize data integrity. A comprehensive SPL syntax reference is included, as are more than 20 stored procedures that can be used or adapted by the reader.